RIG-I-like receptors and negative-strand RNA viruses: RLRly bird catches some worms - Weber, Michaela (Cytokine Growth Factor Rev, 2014)
Negative strand RNA viruses with a nonsegmented genome (ns-NSVs) or a segmented genome (s-NSVs) are an important source of human and animal diseases. Survival of the host from those infections is critically dependent on rapidly reacting innate immune responses. Two cytoplasmic RNA helicases, RIG-I and MDA5 (collectively termed RIG-I-like receptors, RLRs), are essential for recognizing virus-specific RNA structures to initiate a signalling cascade, resulting in the production of the antiviral type I interferons. Here, we will review the current knowledge and views on RLR agonists, RLR signalling, and the wide variety of countermeasures ns-NSVs and s-NSVs have evolved. Specific aspects include the consequences of genome segmentation for RLR activation and a discussion on the physiological ligands of RLRs.